Microbiological and immunological diagnostic criteria for initial degree of generalized periodontitis at the stage of pre X-ray manifestations. - I. S. Mashchenko; V. I. Struk; N. V. Vatamanyuk (Medičnì Perspektivi, 2016)
The article presents the results of a comparative study of the microbial landscape and violations of local immunity in patients with generalized periodontitis at preclinical-radiological stage of development in 60 patients. It was revealed that appearance of representatives of the major periodontal bacteria in the gum tissue is a precursor of development of initial stage of generalized periodontitis in them. It has been established that the early objective indicators of bone resorptive process in periodontal tissues in patients with generalized catarrhal gingivitis is an overproduction of proinflammatory cytokines IL-1.beta and TNF-alpha and the lack of anti-inflammatory IL-4, which persists for a long time during the observation period.